Opening the pathways to scholarly enhancements of teaching and learning - Ciccone, Tony; Hutchings, Pat (Teaching and Learning Inquiry, 2016)
This short piece, written on behalf of the Publications Advisory Committee (PAC), celebrates Teaching & Learning Inquiry’s transition to open access and what that means for the future of the Scholarship of Teaching and Learning. Members of the PAC are Pat Hutchings (US, chair), Sean Brawley (Australia), Mick Healey (UK), Margy MacMillan (Canada), Rebecca Nowacek (US), Tony Ciccone (US), and (ex officio) TLI co-editors Nancy Chick and Gary Poole.